Analisis Keterlaksanaan Pratikum yang Disesuaikan dengan Gaya Belajar Kinestetik - Ritonga, Yemima; Sari, Novi Fitriandika; Chastanti, Ika (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to analyze the implementation of biology practicum adapted to the kinesthetic learning style of students at Kemala Bhayangkari Private High School and evaluate its effectiveness in improving understanding of biological material. The method used was descriptive quantitative with a qualitative approach through interviews, observations, and distributing questionnaires to students of class XI IPA who were selected by purposive sampling. The questionnaire instrument consisted of 25 statements to measure five indicators of practicum implementation, namely problem solving, physical involvement, discussion and reflection, practical activities, and use of tools and materials. The results showed that the level of practicum implementation was in the high category for indicators of problem solving (90.32%), physical involvement (88.41%), discussion and reflection (87.53%), and practical activities (86.45%). Meanwhile, the indicator of the use of tools and materials was in the medium category (77.09%). These findings suggest that practicum tailored to kinesthetic learning styles can support students' active engagement and contribute positively to material understanding. Thus, kinesthetic learning style has a positive relationship with the effectiveness of biology practicum and student learning achievement, so it is important for teachers to design learning that is aligned with the characteristics of this learning style.